On local resonance of fiber-reinforced elastic metacomposites. (October 2022) - Ru, C.Q.
Abstract: A direct method is presented to develop simple analytical model for dynamics of stiff unidirectional fiber-reinforced random metacomposites based on the concept of the displacement field of the mass center of representative unit cell. The developed model is characterized by a modified form of the classical elastodynamic equations combined with a simple differential relation between the displacement field of the composite and the displacement field of the mass center of representative unit cell. A simple formula is derived for the local resonance frequency (see formula (20)). The efficiency and accuracy of the present model are demonstrated by good agreement (with relative errors not more than 10%) between the predicted local resonance frequency and various known data reported in relevant articles published by different research groups in the past two decades (as shown in Table 1). Highlights: Compared to existing models, the present model enjoys conceptual and mathematical simplicity. The model is featured by a modified form of classical elastodynamic equations combined with a simple differential relation between two displacement fields. A simple formula given by the present model is in good agreement with a large group of known data. This model could offer a general new method for dynamics of fiber-metacomposites.